Die Wirkung internationaler Institutionen: Von der Normanerkennung zur Normeinhaltung - Tanja A. Börzel; Thomas Risse (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
– This contribution examines the mechanisms for inducing compliance with international norms and rules as one major form of institutional effects. More specifically, it tackles the process from norm recognition to norm compliance. Two social logics of institutional impact are distinguished. They share the common assumption that only “inconvenient” rules cause problems of non-compliance, since they either cause material and ideational costs or are not compatible with existing institutions and identities. Rationalist approaches concentrate on positive and negative incentives to induce behavioural changes. International institutions can deploy sanctions but also provide resources for strengthening the capacity necessary to comply. Compliance is further promoted if international norms and rules empower actors that favour domestic change. Constructivist approaches, by contrast, conceive of compliance as a process of norm internalization that affects actors' preferences. The legitimacy of international norms and rules, their internalization in domestic law, and the persuasion of “norm-entrepreneurs” are crucial factors in inducing compliance. Although rationalist and constructivist emphasize different logics of social action, their hypotheses about the impact of institutions are not mutually exclusive but relate to each other. Two case studies on compliance with European environmental law and international human rights norms illustrate how rationalist and constructivist compliance mechanisms may interact. The chapter concludes with some suggestions for future research on the effects of international institutions.
Keywords: 330; Normbefolgung; Menschenrechte; Theorie; Welt; EU-Staaten; Internationales Recht; EU-Umweltpolitik